Two Notes on Xie He's 謝赫 "Six Criteria" (liufa 六法), Aided by Digital Databases. - Goldin, Paul R. (T'oung Pao, 2018)
This article uses evidence from digital databases to re-examine two controversial issues regarding the "Six Criteria" (liufa 六法) of painting listed by Xie He 謝赫 (d. after 532) in the preface to his Gu huapin lu 古畫品錄: (1) their syntax and phrasing, and (2) the origin and connotations of qiyun 氣韻, the most famous of the six. Despite recent claims to the contrary, the series of six numbered clauses taking the form "X, Y shi ye 是也" is unremarkable for the language of the time; moreover, the application of the Six Criteria in the subsequent biographies discloses that they are listed in decreasing order of importance. While the meaning and connotations of qiyun are impossible to state succinctly because they vary from one source to another, it is used (like similar phrases, such as yayun 雅韻 and shenyun 神韻) both to praise people's character and as an aesthetic quality pertaining to music, literature, and art.